Development of spectrum management tool using open-source geographical information system (GIS) software - Saman, Mohamad Afif; Ismail, Ahmad Fadzil; Mohd Sobli, Nuurul Hudaa; Atiqullah Fakrullah, Ahmad Nasruddin; Hashim, Wahidah (AENSI Publications, 2014)
Mobile communication is one of the fastest evolving technologies in theworld. With the availability of new services and applications, the demand for spectrumaccess is increasing. However since the spectrum is a limited source, a proper planningto accommodate this demand is required. Proprietary spectrum management software isexpensive and not a cost effective solution in a long run. It is also too rigid to adaptwith the mobile communication rapid evolution. There is a need for low cost home-grown spectrum management tool that can assist regulatory body in spectrummanagement process. The tool must be able to help in managing existing spectrum andalso for new spectrum planning. This paper outlines the use of open-source resources todevelop the proposed tool. The tool incorporates and embeds the rules and regulationsspecified by Malaysian authority. The home-grown tool is able to carry out spectrumplanning and management for 2G, Global System for Mobile Communications (GSM),and 3G, Universal Mobile Telecommunications System (UMTS) networks